Security analysis and resilient control of discrete-event systems - Tai, Ruochen (Nanyang Technological University, 2023)
Cyber-physical systems (CPS) have been playing significant roles in modern society due to their precise control, remote collaboration, and autonomous functions. The realization of these powerful features heavily relies on the network system (cyber part), which, however, brings about two potential risks. Firstly, the information transmitted through the network might be compromised to cause irreparable damage by the smart active adversary (attacker), which covertly performs malicious attack operations, e.g., sensor/actuator signals modification, without being detected. Secondly, the information flow might be intercepted to cause privacy leakage by the passive adversary (intruder), which uses its observations to infer the system secret. Hence, studying security issues is of great significance and practical application value to the safe and resilient operation of CPS.